Prevalence, Incidence, and Clearance of Anogenital Warts in Kenyan Men Reporting High-Risk Sexual Behavior, Including Men Who Have Sex With Men. (12th May 2015) - Neme, Santiago; Wahome, Elizabeth; Mwashigadi, Grace; Thiong'o, Alexander N.; Stekler, Joanne D.; Wald, Anna; Sanders, Eduard J.; Graham, Susan M.
Abstract: Background.  Human papillomavirus (HPV) causes a spectrum of disease, ranging from warts to cancer. Prevalence, incidence, and factors associated with anogenital warts in East African men are unknown. Methods.  Kenyan men reporting high-risk sexual behavior were inspected for anogenital warts at enrollment and follow-up visits. Logistic regression was performed to identify associations with anogenital warts at baseline. Cox regression was performed to analyze predictors of incident anogenital warts, and Kaplan–Meier curves were used to estimate clearance. Results.  Baseline anogenital wart prevalence in 1137 men was 2.9% (95% confidence interval [CI], 2.0%–4.0%) overall, 2.0% in human immunodeficiency virus (HIV)-uninfected men, and 9.4% in HIV-1-infected men (adjusted odds ratio, 5.43; 95% CI, 2.03–11.29). Over a median of 1.4 years, anogenital wart incidence among 1104 men was 5.3 (95% CI, 4.3–6.5) per 100 person-years. Having HIV-1 infection at baseline (adjusted hazard ratio [aHR], 1.66; 95% CI, 1.01–2.72) or a genital syndrome during follow-up (aHR, 4.78; 95% CI, 3.03–7.56) was associated with increased wart incidence. Wart clearance was lower in HIV-1-infected men (log-rank P <.001). Conclusions.  Anogenital wart prevalence and incidence were increased in HIV-1-infected men, and anogenital warts co-occurred with other genital syndromes. Quadrivalent HPV vaccination should be recommended for young men in settings with high HIV-1 prevalence.